2008
DOI: 10.3144/expresspolymlett.2008.34
|View full text |Cite
|
Sign up to set email alerts
|

Modification of PTFE nanopowder by controlled electron beam irradiation: A useful approach for the development of PTFE coupled EPDM compounds

Abstract: Abstract. Low-temperature reactive mixing of controlled electron beam modified Polytetrafluoroethylene (PTFE) nanopowder with Ethylene-Propylene-Diene-Monomer (EPDM) rubber produced PTFE coupled EPDM rubber compounds with desired physical properties. The radiation-induced chemical alterations in PTFE nanopowder, determined by electron spin resonance (ESR) and Fourier transform infrared (FTIR) spectroscopy, showed increasing concentration of radicals and carboxylic groups (-COOH) with increasing irradiation dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Radiation induced grafting offers some unique advantages over the conventional chemical grafting method since it results in uniform grafting and it is room a temperature process [4]. Radiation grafted co-polymers have been tried for a wide spectrum of applications like surface modification [5], separation purposes [6], biotechnology [7], electrochemical applications such as electro-dialysis [8], battery separator [9] and solid polymer electrolyte in fuel cells [10]. Ion exchange membranes have been investigated for their suitability as battery separator because of their durability, long life, high charge density and appreciable ion exchange capacity at optimum water content, which is the most desirable property of the separator membranes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation induced grafting offers some unique advantages over the conventional chemical grafting method since it results in uniform grafting and it is room a temperature process [4]. Radiation grafted co-polymers have been tried for a wide spectrum of applications like surface modification [5], separation purposes [6], biotechnology [7], electrochemical applications such as electro-dialysis [8], battery separator [9] and solid polymer electrolyte in fuel cells [10]. Ion exchange membranes have been investigated for their suitability as battery separator because of their durability, long life, high charge density and appreciable ion exchange capacity at optimum water content, which is the most desirable property of the separator membranes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation functionalization produces PTFE micropowders containing persistent trapped-radicals radicals and functional groups on the surface of PTFE powder can be easily compounded into elastomers such as EPDM rubber. A detailed characterization related to the mechanical, friction and wear properties of PTFE-based EPDM compounds have been presented by the authors in [20,21]. In previous attempts the spectroscopic investigations revealed that during peroxide vulcanization the radiationinduced chemical changes in PTFE powder result in lower crosslinking efficiency and ultimately poor bulk properties of PTFE-EPDM composites [22,23].…”
mentioning
confidence: 99%
“…Reinforcement of rubber by CB has been intensively studied. It is generally accepted that the reinforcement of elastomers and the improvement of other properties, to a large extent, are associated with the chemical and physical interactions between the polymer matrix and CB .…”
Section: Introductionmentioning
confidence: 99%